The Impact of Government Revenue on the Achievement of the Sustainable Development Goals and the Amplification Potential of Good Governance - O’Hare, Bernadette; G. Hall, Steve (Central European Journal of Economic Modelling and Econometrics, 2021)
The United Nations General Assembly established the Sustainable Development Goals in 2015 to achieve an equitable and sustainable future for all by 2030. This study aims to model the relationship between government revenue per capita, quality of governance and the targets of several of these goals, including the coverage of the critical determinants of health; water, sanitation, healthcare, and education. We used government revenue because the policies and practices of international and multinational organisations – including corporations and banks – are more likely to influence revenue rather than government spending in countries in which they are engaged. Also, government revenue reflects a government’s ability to spend across all sectors rather than just health or education. An unbalanced non-linear panel data model was employed, and annual data on 217 countries over the period 1960– 2000 was used. The coverage of the Sustainable Development Goal variables was expressed as percentages and measures of the quality of governance included in the model. A linear relationship between revenue and the determinants of health would not be appropriate; therefore, we employ a logistic function. A standard panel logistic function would impose the same shape “S” curve on all countries, which is inappropriate. Therefore, we augment the parameters of the logistic function with measures of the quality of governance in each country, which allows each country to have a different “S” shape as the quality of its governance varies. Our study found that increased government revenue is associated with increased progress towards the Sustainable Development Goals. An improvement in the quality of governance could amplify this effect. This modelling and its accompanying visualisations can predict the potential of an increase in government revenue in an individual country regarding progress towards the Sustainable Development Goals.